Developing a tactical irrigation and nitrogen fertilizer management strategy for winter wheat through drip irrigation - Zain, Muhammad; Si, Zhuanyun; Ma, Haijiao; Cheng, Minghan; Khan, Adam; Mehmood, Faisal; Duan, Aiwang; Sun, Chengming (Frontiers in Plant Science, 2023)
Agricultural activities in North China Plain are often challenged by inadequate irrigation and nutrients supply. The inadequate and improper resource utilization may impose negative impacts on agricultural sustainability. To counteract the negative impacts, a deeper understanding of the different resource management strategies is essential prerequisite to assess the resource saving potential in crops. We explored plausible adaptation strategies including; drip irrigation lateral spacings of 40 cm and 80 cm (hereafter referred as LS40 and LS80 respectively), irrigating winter wheat after soil water consumption of 20 mm and 35 mm (hereafter represented as IS20 and IS35 respectively), and nitrogen fertilization scheme of (a) applying 50% nitrogen as basal dose and 50% as top-dressing dose (NS50:50), (b) 25% nitrogen as basal dose and 75% as top-dressing (NS25:75), (b) no nitrogen application as basal and 100% application as a top-dressing (NS0:100).The consecutive 2-years (2017-2018 and 2018-2019) field study results shows that, growing winter wheat under LS40 evidently enhanced the water use efficiency (WUE), grain yield, water use efficiency (WUE), 1000-grain weight, and number of grains per spike by 15.04%, 6.95%, 5.67%, and 21.59% during 2017-2018 season respectively. Additionally, the corresponding values during 2018-2019 season were 12.70%, 7.17%, 2.66%, and 19.25% respectively. Irrigation scheduling of IS35 treatment improved all the growth related and yield parameters of winter wheat. Further, treating 25% nitrogen as basal and application of 75% as top-dressing positively influenced the winter wheat yield. While NS0:100 increased the plant height, leaf area index (LAI), and aboveground biomass as compared to the other application strategies, but high nitrogen was observed in deeper soil layers. Regarding soil environment, lowest soil moisture and nitrate nitrogen contents were observed in LS80 during both growing seasons. Overall, coupling the IS35 with NS25:75 under 40 cm lateral spacing is a suitable choice for sustainable winter wheat production in the North China Plain. The results of our study may be helpful in advancing the knowledge of farmer community for winter wheat production. The findings can also aid in advancing the new intuitions among scientists working on soil water and nitrogen distribution in drip irrigation for better productivity.